2013
DOI: 10.1186/1472-6963-13-223
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Physician Assistants in primary care: a systematic review

Abstract: BackgroundPrimary care provision is important in the delivery of health care but many countries face primary care workforce challenges. Increasing demand, enlarged workloads, and current and anticipated physician shortages in many countries have led to the introduction of mid-level professionals, such as Physician Assistants (PAs). Objective: This systematic review aimed to appraise the evidence of the contribution of PAs within primary care, defined for this study as general practice, relevant to the UK or si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 45 publications
3
77
1
Order By: Relevance
“…The deployment of PAs in UK primary care to patients attending mainly same-day appointment surgeries has been reported qualitatively before 72 and confirmed here, similar to the international literature. 176,193 The lack of legal authority to prescribe in the UK deterred the GPs and practice managers from deploying PAs to home visits. This concurs with evidence from previous studies in the UK.…”
Section: Inter-rater Reliabilitymentioning
confidence: 99%
“…The deployment of PAs in UK primary care to patients attending mainly same-day appointment surgeries has been reported qualitatively before 72 and confirmed here, similar to the international literature. 176,193 The lack of legal authority to prescribe in the UK deterred the GPs and practice managers from deploying PAs to home visits. This concurs with evidence from previous studies in the UK.…”
Section: Inter-rater Reliabilitymentioning
confidence: 99%
“…Each PA's scope of practice is defined by what has been delegated to them by their supervising physician and guided by a National Competency Profile that defines how and under what circumstances the PA may exercise their competencies (Mikhael, There is limited research evidence about the efficacy of PAs in any context, but most of what exists is primarily relevant to the American healthcare context, creating difficulty in finding generalizable, transferable evidence about PA performance that is useful to Canadian decision-makers (Doan et al 2011;Halter et al 2013;Kleinpell, Ely and Grabenkort 2008). Systematic reviews of evidence about PAs in the context of primary care, intensive care, and emergency care have demonstrated that most existing publications focus on describing the types of tasks and roles that PAs are employed in, and very little generalizable evidence is available about their efficacy at performing those tasks, impact on patient outcomes, or cost-effectiveness (Doan et al 2011;Halter et al 2013;Kleinpell, Ely and Grabenkort 2008). These systematic reviews comment on the difficulty of comparing or synthesizing the data that do exist, due to the heterogeneous contexts in which PAs work and the challenge of extracting PA data from that related to other health care providers.…”
Section: History and Contextmentioning
confidence: 99%
“…213,214 Like NPs, PAs' emergence sprung in the late 1960s to fill physician shortages, specialty maldistributions as physicians shifted to specialty practices 186 , and geographical maldistributions. 215 After the Korean War, the PA profession took returning…”
Section: Find Someone Else: Physician Assistantsmentioning
confidence: 99%
“…186,215,216 PAs' influence on unmet healthcare needs was meaningful, although diminished by there being fewer than 20,000 actively practicing PAs until the 1990s. 216 A "primary care"-focused healthcare system that became vogue in the 1990s called for the PA profession to increase its numbers.…”
Section: Find Someone Else: Physician Assistantsmentioning
confidence: 99%
See 1 more Smart Citation